Pengaruh Lama Perendaman Terhadap Proses Perkecambahan Biji Jagung (Zea Mays) - Apriani Hia (CV. SINAR HOWUHOWU, 2025)
Seed soaking is one of the pre-planting treatments aimed at improving germination rate and accelerating plant growth. This study aims to evaluate the effect of soaking duration on the germination process of corn (Zea mays) seeds. The method used in this research was a completely randomized design (CRD) with four soaking duration treatments: 0 hours, 6 hours, 12 hours, and 24 hours, each repeated three times. The observed parameters included germination rate, growth speed, and seedling length. The results of this study indicated that soaking duration had a significant effect on the germination rate and early growth of corn seeds. The 12-hour soaking treatment produced the most optimal results, with the highest germination rate and the best seedling growth.